Morfologia, patogenicidade e sensibilidade à fungicidas de isolados de Colletotrichum truncatum (Schw.) Andrus & WD Moore - Guimarães, Gesiane Ribeiro Guimarães (2021)
Anthracnose from soy (Glycine max L.) occurs in all areas of soy production in the world. Among the factors that limit the achievement of high soybean yields are diseases. Anthracnose is one of the main diseases of the crop, being caused by the fungus Colletotrichum truncatum. In the first chapter, isolates of Colletotrichum truncatum were obtained from several hosts, coming from different soy producing regions. Pure cultures were obtained and inoculated in leaves, stems and pods detached. Regarding mycelial staining, there was variation in the appearance of the C. truncatum colony. The rate of mycelial growth among the isolates ranged from 8.5 mm.day-1 (isolated from Passo Fundo-RS) to 9.10 mm.day-1 (isolated from Passo Fundo-RS), demonstrating a smaller and greater physiological activity, respectively, of the isolates under artificial conditions. In the stem, the isolates that showed less injury and that differed statistically from the others were the isolates Passo Fundo-RS, Brasilia-DF and Urutaí-GO, 12 were less aggressive compared to the others with lesions ranging from 33.46 to 35.10 mm. length. The most aggressive produced injuries from 35.38 to 37.55 mm in length. On the leaf the most aggressive isolate was the Brasília-DF isolate, the lesion reached 79.99 mm in length, followed by the Passo Fundo-RS, Brasilia-DF and Urutaí-GO isolates. In the pod, the most aggressive isolate was the Brasília-DF isolate, the lesion reached 49.79 mm in length and the least aggressive were the Passo Fundo-RS and Urutaí isolates. In chapter 2, the objective was to evaluate the effect of temperature on the isolates. The plates were subjected to incubation at a temperature of 20º; 25th; 27th; 32nd; and 35ºC, under 12 h photoperiod, for seven days in BOD. The evaluation of mycelial growth was made by measuring every 24 h, recording the diameter in millimeters of the colonies in an orthogonal position, for seven days from the moment the mycelium discs containing the isolate were placed. Statistical analyzes were performed in the statistical program R. The significant variables in the F test of the analysis of variance were subjected to the means test and to the regression analysis. The isolates showed different behavior in the speed of mycelial growth with adaptive capacity at different temperatures. In chapter three, the objective of the work was to evaluate in vitro the sensitivity of different isolates of C. truncatum collected in different locations, the fungicides of different active ingredients incorporated to the BDA at concentrations of 0; 0.1; 1.0; 10 and 100 ppm. The percentage of the fungus was evaluated when subjected to fungicides: pyraclostrobin + fluxpyroxade + epoxiconazole, trifloxystrobin + protioconazole and pyraclostrobin + fluxpyroxade to establish which one had the highest control efficiency. It is possible to verify the great variability of sensitivity of C. truncatum isolates present before the different molecules and the importance of detecting resistant populations.